Exposing EFL Students’ FLRA in Reading Section: The Case of TOEFL Course - Fatin Nadifa Tarigan; Dian Heriani; Anni Alvionita Simanjuntak; Siti Aminah Hasibuan (Association of Language Teachers in Southeast Asia (ALTSA), 2023)
Foreign Language Reading Anxiety (FLRA) becomes increasingly crucial for EFL students since it prevents the learners' reading grasp. This study reports on college students’ reflections on reading. The study's main objective was to determine students' reading anxiety levels and discover the most potential factors contributing to students’ Foreign Language Reading Anxiety (FLRA) in TOEFL Test. It was administered to 22 students of the English Department in Universitas Pembinaan Masyarakat Indonesia using purposive sampling in the academic year 2022/2023. To achieve this purpose, this study utilized both quantitative and qualitative approaches. The data were collected using a Foreign Language Reading Anxiety Scale (FLRAS) questionnaire with five-point Likert scale participants and an interview sheet to examine the levels of their reading anxiety and its factors. The results demonstrate that the student's reading anxiety levels were 18% in the low category, 64% in the medium category, and 18% in the high category. It indicates that they experienced a medium level of anxiety while reading with unfamiliar vocabulary and unknown topics, and the fear of making mistakes was identified as the significant factor of FL reading anxiety.